Supreme Court Opinions and Audiences - Ryan C. Black; Ryan J. Owens; Justin Wedeking; Patrick C. Wohlfarth (Washington University Journal of Law & Policy, 2017)
This Article evaluates different rhetorical strategies Supreme Court justices employ in writing their opinions for specific audiences. Black, Owens, Wedeking, and Wohlfarth suggest justices keep lower federal courts, state governments, federal bureaucratic agencies, and the public in mind when crafting decisions, particularly to ensure compliance with the decision and avoid non-compliance. The Article identifies opinion clarity as a means of ensuring lower federal courts will follow precedent, as well as a way for smaller and less sophisticated bureaucratic agencies to avoid shirking the Court’s rulings. The Article concludes judicial clarity is only one of an arsenal of rhetorical devices used by the Supreme Court justices, and further evaluation and research may be helpful.
Keywords: Supreme Court; Roberts Court; Opinions; Audience Effect; Rhetoric; Strategy